Ordering and Pacifying: A Fundamental Urban Ambivalence Based on the Water Paradox, South Asia, Tenth–Sixteenth Century - Keller, Sara (History of religions, 2025)
In South Asia, waterscapes were fundamental elements of urbanity, as they not only constituted the visual identity of cities but also supported narratives and practices of urban life. These waterscapes drew on references to the classical and purāṇic Sanskrit literature presenting water as a sacred element related to fertility, health, and spiritual purification. However, an attentive look at historical and archaeological sources from the medieval and early modern period provides a more complex picture: water meant amṛta (essence of life) just as it meant mṛtyu (death). Focusing on the paradoxical meanings of water during the third urbanization phase (ca. tenth to sixteenth century), this article questions the urban approach to nature and matter in South Asia, in which water was the metaphor. It shows that the paradox of water (hydrophilia vs. hydrophobia) rested on an ambiguous relationship to a natural environment that was both sought and feared. Urban life responded to this paradoxical relationship to nature with a fundamental and unresolved, yet productive, ambivalence toward what I will call "ordering" and "pacifying." While ordering attitudes aimed to segment, limit, and regulate matter in order to keep it under control, pacifying attitudes aspired to aggregate, support, and nurture matter in order to let it grow or expand. In South Asia, the ambivalence, or never-resolved tension between "ordering" and "pacifying," was responsible for the production of rich and changing urban water cultures.